Determination of heavy metal concentration in top surface and sub surface soil around Ulu Tualang closed landfill, Temerloh Pahang - Ahmad Khusairi, Ayop (2010)
There are variety type of heavy metal may contain in the soil at the landfill. Heavy metal is the metallic chemical element that has a relatively high density and it is toxic and poisonous at low concentrations. The objectives of this research are to determine and analyses the distribution of heavy metal that present in the soil obtained from newly-closed landfill at Ulu Tualang Temerloh and to determine which heavy metal have higher amount of concentration in sub and top surfaces of the soil and also to compare it with the Environmental Protection Agency (EPA) Compost Standard. Heavy metal that will be analyses is zinc (Zn) and lead (Pb). For this experiment, after we pulverized and sieved the sample, we extract the sample using Acid Digestion Method, then both Zn and Pb concentration in the sample is determined using Atomic Absorption Spectroscopy (AAS). The result obtained is concentration of Pb in the soil is in range 5.65 mg/kg to 60.6 mg/kg while concentration range of Zn is between range 0.761 mg/kg to 16.365 mg/kg. As a conclusion, for overall the concentration of Pb is highest compared to Zn in top and sub surface of the soil and this heavy metal distribution data is under EPA Compost Standard (Zn and Pb) and also is very useful to be a good reference and guideline for soil remediation.